KEKERASAN DALAM PENGASUHAN DAN DAMPAKNYA PADA KESEHATAN MENTAL ANAK: SEBUAH KAJIAN HOLISTIK - Siti Rahmah; Ernawulan Syaodih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines violence in caregiving as a serious problem that negatively impacts child development. Violence against children includes physical, emotional, verbal, symbolic, and sexual acts that cause physical, psychological, or sexual harm. The study used a literature review method to identify the causes of violence in caregiving, such as economic stress, lack of parental education, a history of family violence, and mental health problems in parents. Using Bandura's social learning theory, the study sought to understand how violent behavior can be learned and imitated within the family environment, and how interventions can be designed to change these behavioral patterns. The findings indicate that violence in caregiving contributes to psychological disorders such as anxiety, depression, and PTSD in children. Effective prevention and intervention strategies include parent education, social support, mental health services, and public policies that support families. In addition, parent education and support programs, early intervention, and public awareness campaigns can help reduce the incidence of violence and improve child well-being. This study emphasizes the importance of a holistic and multisectoral approach to addressing violence in caregiving, with the goal of creating a safe and supportive environment for healthy and happy child development.